Novel genetic loci associated with hippocampal volume - Derrek P. Hibar (Nature Portfolio, 2017)
The hippocampus in mammalian brain varies in size across individuals. Here, Hibar and colleagues perform a genome-wide association meta-analysis to find six genetic loci with significant association to hippocampus volume.